Konservasi penyu di Pulau Talise, Gangga dan Bangka Kabupaten Minahasa Utara - Arunde, Preti; Boneka, Farnis B.; Wagey, Billy Th.; Mamangkey, Gustaf; Manembu, Indri; Kambey, Alex (e-Journal BUDIDAYA PERAIRAN, 2018)
Generally, this study was intended to examine the problems or implementation of turtle conservation in Talise, Gangga and Bangka Islands and specifically with a number of objectives to: know the introduction of sea turtle, to know sea turtle fishing and turtle exploitation, to know the knowledge of the people about turtle as a protected animal. Survey results on Talise Island, Gangga and Bangka showed that people who had seen turtles directly: Talise Island 94%, Gangga 58%, and Bangka 92%. Local residents of Talise, Gangga and Bangka Islands know well the turtles even see directly in their habitat and spawning time. In Talise, Gangga and Bangka Islands, turtles are still commonly caught, traded and consumed by local people. People's awareness about turtles as protected animals is lacking. Keywords: Turtle, Talise Island, Gangga and Bangka